Chapter 9 Evaluations of 'opportunity' versus 'risk' Vietnamese migrants' experiences and perceptions of the UK border - Barber, Tamsin (2024)
The plight of Vietnamese migrants in the UK has featured prominently in recent media and public policy debates on modern slavery, illegal border crossings, and labour exploitation. Yet little attention has been paid to their subjective experiences of border crossings, nor the wide range of categories they pass between. Vietnamese migrants coming to the UK in search of work face a complex array of decisions surrounding the respective costs and risks related to a chosen migration route which must be weighed against personal and collective expectations. These complex decisions are compounded by a shifting and highly stratified immigration and borders regime which renders migrants more vulnerable through restricting rights and increasing surveillance. This chapter explores the experiences and imaginaries of the UK border among migrants who have crossed the UK border, as well as those who intend to make the journey. We explore the contrast between the expectations and realities of UK borders through in-depth interviews with Vietnamese migrants. We argue, notwithstanding knowledge of the risks involved in border crossings and the hostile border enforcement regime, imaginations of opportunities for transforming local livelihoods remain powerful and deep-seated political and cultural narratives for Vietnamese migrants.